Electoral rules and politicians' behavior: a micro test - Stefano Gagliarducci; Tommaso Nannicini; Paolo Naticchioni (Institute for the Study of Labor (IZA), 2008)
Theory predicts that the majoritarian electoral system should produce more targeted redistribution and lower politicians' rents than proportional representation. We test these predictions using micro data for the mixed-member Italian House of Representatives, which allow us to sidestep the identification problems of previous studies based on country-level data. In particular, we address the nonrandom selection into different electoral systems by exploiting a distinctive feature of the Italian two-tier elections from 1994 to 2006: candidates could run for both the majoritarian and the proportional tier, but if they won in both tiers they had to accept the majoritarian seat. Focusing on elections decided by a narrow margin allows us to generate quasi-experimental estimates of the impact of the electoral rule. The main results confirm theoretical predictions, as majoritarian representatives put forward a higher proportion of bills targeted at local areas and show lower absenteeism rates than their proportional colleagues.
Keywords: C20; 320; Electoral rule; politicians; targeted redistribution; rent-seeking; regression discontinuity design; treatment effect; Politiker; Verhalten; Wahlsystem; Regionalpolitik; Wahlkreis; Rent Seeking; Italien